Issues of Establishing GeRaNIUM Grid Portal in the GeRaNIUM Project - Arifin, A.; Sun, L.C. (2007)
GeRaNIUM Grid Portal is a portal developed consequently for University of Malaya campus-wide computational grid project which is coined as GeRaNIUM, an acronym for Grid-Enabled Research Network and Infostructure of the University of Malaya. The portal development aims to provide a platform for researchers to access their collective resources, skills, experiences and results in a secure, reliable and scalable manner. GeRaNIUM Grid Portal provides seamless integration of myriad of heterogenous applications and datasets that span multiple administrative domains and locations across the globe, and presents these to researcher through a user friendly interface.